Phenylephrine causes anuria in a patient with benign prostatic hyperplasia - Sahu, Pratap Kumar; Kumar Dash, Mahesh; Kpeno, Audifax (International Journal of Research in Medical Sciences, 2024)
Phenylephrine is classified as an alpha-adrenergic agonist and used as a nasal decongestant. Benign prostatic hyperplasia (BPH) is a common progressive disease in males over the age of 40, leading to urethral constriction. Alpha-1A (α1A) receptor blockers such as Silodosin are commonly prescribed to manage BPH symptoms. They relax the smooth muscle around the bladder exit, in the lower urinary tract and prostate gland to facilitate the passage of urine in BPH. However, when combined with alpha-adrenergic agonists such as Phenylephrine, this mechanism may be disrupted. This case report highlights contraindication of Phenylephrine in patients with BPH. It may induce anuria in patients with BPH. We present a case report of a diabetic, hypertensive and hypothyroidism patient with BPH suffering from anuria due to administration of an over-the-counter medicine containing Phenylephrine. Caution should be taken while prescribing Phenylephrine in BPH patients on medication with alpha-1A (α1A) receptor blockers.